If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = 5x + 25 Reorder the terms: 90 = 25 + 5x Solving 90 = 25 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 90 + -5x = 25 + 5x + -5x Combine like terms: 5x + -5x = 0 90 + -5x = 25 + 0 90 + -5x = 25 Add '-90' to each side of the equation. 90 + -90 + -5x = 25 + -90 Combine like terms: 90 + -90 = 0 0 + -5x = 25 + -90 -5x = 25 + -90 Combine like terms: 25 + -90 = -65 -5x = -65 Divide each side by '-5'. x = 13 Simplifying x = 13
| 2s+4=5(14-2s) | | 12000*.0127= | | -15+-r=30 | | -10(-3h-2)-10(-2h-9)= | | -8.4(x-2.75)=25.2 | | -6(4-8s)=20 | | 6.4x-3.5=52.2 | | F+v-e=2fore | | 1.6=-0.3 | | 7y+4x-2=0 | | .073x+.0127(12000-x)=1308 | | 25500+2000=47900-800 | | 9=0+0 | | 34+a=62 | | -3x-1=-10x-8 | | 4xy^4z^3-4xy^4z^3= | | M-56=10 | | 12x-8=-308 | | -5(t-3)-(t+1)=3 | | 7k+10-15-4K=-13 | | h+14=33 | | 9x-6=4x+1 | | 2500=x^4 | | 0.5(4z+7)+17.7=0.7(4z-4) | | 6x-2+3x=4x-3+4x | | 17-3m=8 | | 3x+8+2=19 | | 28+h=44 | | 35x-1=20x+2 | | 66x+4=-2 | | (8x-12)=6x+8 | | -2x^2-9x+35=0 |